Melioidosis acquired by traveler to Nigeria. - Salam, A; Khan, N; Malnick, H; Kenna, D; Dance, D; Klein, J (Centers for Disease Control and Prevention, 2011)
We describe melioidosis associated with travel to Nigeria in a woman with diabetes, a major predisposing factor for this infection. With the prevalence of diabetes projected to increase dramatically in many developing countries, the global reach of melioidosis may expand.